2005
DOI: 10.1007/s10740-005-0080-x
|View full text |Cite
|
Sign up to set email alerts
|

An Axisymmetric Flow of a Mixture of Real Gases with a Condensing Component

Abstract: A synthesized physicomathematical model of a binary mixture of real gases with a condensing component is used to perform numerical investigations of axisymmetric flow in nozzles of different geometry. The effect is investigated, which the model of state for gas makes on the position of the "condensation jump", on the mass spectrum of droplets, and on the flow rate realized by nozzles of preassigned geometry. Comparison of numerical results is made for the Redlich-Kwong and Mendeleev-Clapeyron models and for tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…The vertical line x=x* confirms that, for both cases, the Mach number value of unity is obtained at the critical cross section of the nozzle. This conclusion agreed very well with the predictions in recent studies (Arina, 2004, Molleson & Stasenko, 2005, and Drikakis & Tsangaris, 1993. It can, therefore, be concluded that the sonic position always occurs at the throat and is independent of the nozzle geometry and gas thermodynamic model.…”
Section: Geometry Influencesupporting
confidence: 91%
See 3 more Smart Citations
“…The vertical line x=x* confirms that, for both cases, the Mach number value of unity is obtained at the critical cross section of the nozzle. This conclusion agreed very well with the predictions in recent studies (Arina, 2004, Molleson & Stasenko, 2005, and Drikakis & Tsangaris, 1993. It can, therefore, be concluded that the sonic position always occurs at the throat and is independent of the nozzle geometry and gas thermodynamic model.…”
Section: Geometry Influencesupporting
confidence: 91%
“…1. Nozzle geometries studied in the research Figure 2 shows the variation of Mach number with position in real case and the comparison with results obtained from the work of Molleson and Stasenko (2005). One can see that choke (sonic velocity, M=1) occurs at the throat regardless of the EOS used.…”
Section: Results and Discussion 231 De Laval Nozzlesmentioning
confidence: 79%
See 2 more Smart Citations
“…Real gas laws predict the true behaviour of a gas by considering the terms to describe attractions between molecules. The van der Waals (VW) equation which was the first cubic equation to predict the real gas properties was developed in 1873 (Molleson and Stasenko, 2005 (Jacobsen et al, 1997):…”
Section: Equations Of Statementioning
confidence: 99%